Block training periodization in alpine skiing: effects of 11-day HIT on VO2max and performance - Breil, F. A.; Weber, S. N.; Koller, S.; Hoppeler, H.; Vogt, M. (European Journal of Applied Physiology, 2010)
Attempting to achieve the high diversity of training goals in modern competitive alpine skiing simultaneously can be difficult and may lead to compromised overall adaptation. Therefore, we investigated the effect of block training periodization on maximal oxygen consumption (VO2max) and parameters of exercise performance in elite junior alpine skiers. Six female and 15 male athletes were assigned to high-intensity interval (IT, N = 13) or control training groups (CT, N = 8). IT performed 15 high-intensity aerobic interval (HIT) sessions in 11 days. Sessions were 4 × 4 min at 90-95% of maximal heart rate separated by 3-min recovery periods. CT continued their conventionally mixed training, containing endurance and strength sessions. Before and 7 days after training, subjects performed a ramp incremental test followed by a high-intensity time-to-exhaustion (tlim) test both on a cycle ergometer, a 90-s high-box jump test as well as countermovement (CMJ) and squat jumps (SJ) on a force plate. IT significantly improved relative VO2max by 6.0% (P < 0.01; male +7.5%, female +2.1%), relative peak power output by 5.5% (P < 0.01) and power output at ventilatory threshold 2 by 9.6% (P < 0.01). No changes occurred for these measures in CT. tlim remained unchanged in both groups. High-box jump performance was significantly improved in males of IT only (4.9%, P < 0.05). Jump peak power (CMJ -4.8%, SJ -4.1%; P < 0.01), but not height decreased in IT only. For competitive alpine skiers, block periodization of HIT offers a promising way to efficiently improve VO2max and performance. Compromised explosive jump performance might be associated with persisting muscle fatigue.